2005
DOI: 10.1103/physrevb.72.045411
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical switching of the Peierls-like transition in metallic single-walled carbon nanotubes

Abstract: The high-energy vibrational modes of metallic carbon nanotubes are believed to be softened compared to the semiconducting ones by a Peierls-like transition. The Raman modes, when excited with a red laser to enhance the metallic tubes, were found to exhibit an exceptionally high sensitivity to electrochemical doping. Our data may be interpreted as controlling the Peierls-like instability in metallic tubes with the applied potential. We also discuss the limits of applicability of the double-layer charging model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
80
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 32 publications
8
80
1
Order By: Relevance
“…This effect has been observed by many groups 13,15,16 , and generally agrees with phonon renormalization theory quite well 9,17,18,21 . Selected Raman G band spectra from the nanotubes in this study are shown in Figure 1.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…This effect has been observed by many groups 13,15,16 , and generally agrees with phonon renormalization theory quite well 9,17,18,21 . Selected Raman G band spectra from the nanotubes in this study are shown in Figure 1.…”
Section: Introductionsupporting
confidence: 70%
“…The Gband is broadened and downshifted (reduced in frequency), an effect arising from coupling to a continuum of electronic states 9,10,[12][13][14][15][16][17][18] . In other words, the LO phonon mode is damped by the free electrons near the Fermi energy 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…[28,29] However, here we found only a very slight difference between the TG mode of SWCNT and 6T@SWCNT. Therefore, the charge transfer between SWCNT and encapsulated 6T is not significant.…”
Section: Resultscontrasting
confidence: 70%
“…The especially strong electron-phonon coupling in this one-dimensional system has a significant effect on the G band of metallic nanotubes, which gives rise to a Kohn anomaly (KA) [8][9][10][11] , and is even predicted to cause a Peierls distortion (PD) at T=0K 12,13 . The G band for metallic SWNTs consists of two peaks, a G -peak that corresponds to the LO phonon mode and a G + peak, corresponding to the TO phonon mode.…”
mentioning
confidence: 99%
“…Raman spectroscopy 13,[18][19][20] . It is not surprising that the Born-Oppenheimer approximation breaks down in carbon nanotubes, given the fast vibrational motion of their tightly bound carbon atoms (0.02ps) and long electron lifetimes (0.2-3.0ps) 21 .…”
mentioning
confidence: 99%